Disrupted Inhibitory Plasticity and Homeostasis in Fragile X Syndrome - Cea-Del Rio, C (Academic Press, 2020)
Fragile X Syndrome (FXS) is a neurodevelopmental disorder instigated by the absence of a key translation regulating protein, Fragile X Mental Retardation Protein (FMRP). The loss of FMRP in the CNS leads to abnormal synaptic development, disruption of critical periods of plasticity, and an overall deficiency in proper sensory circuit coding leading to hyperexcitable sensory networks. However, little is known about how this hyperexcitable environment affects inhibitory synaptic plasticity. Here, we show that in vivo layer 2/3 of the primary somatosensory cortex of the Fmr1 KO mouse exhibits basal hyperexcitability and an increase in neuronal firing rate suppression during whisker activation. This aligns with our in vitro data that indicate an increase in GABAergic spontaneous activity, a faulty mGluR-mediated inhibitory input and impaired inhibitory plasticity processes. Specifically, we find that mGluR activation sensitivity is overall diminished in the Fmr1 KO mouse leading to both a decreased spontaneous inhibitory postsynaptic input to principal cells and a disrupted form of inhibitory long-term depression (I-LTD). These data suggest an adaptive mechanism that acts to homeostatically counterbalance the cortical hyperexcitability observed in FXS. © 2020